#TITLE_ALTERNATIVE# - (NIM : 13311004); AMANDA CASTOLINA (NIM : 13311005); Pembimbing : Dr. Ir. Sutanto Hadisupad, ISMADINA
Safety aspect in process industries is one of the essential factor that oftenly discussed by for the past few years. Mini plant flow at Industrial Management and Control System Laboratory has been made the main object to understand the concept of Safety Instrumented System (SIS). Another intention of this thesis is also to design a safety system that may improve the reliability of the mini plant's performance. Analysing risk can be attained using the Hazard and Operability Study Analysis and Risk Matrix method. The result of the analysis are 11 deviations that may happen in mini plant flow. One of the deviations, high level in the hot water tank, has the highest risk out of all dangers that may happen. Hence, it is required to install a Safety Instrumented System (SIS) with certain safety level, often called as Safety Integrity Level (SIL) 1. Achieving the best SIS design can be done by changing the SIS's components configurations and systems' architecture. There are 479 results for SIS combinations that can be put into considerations. There are PFDavg values for each SIS's combinations that can be converted to SIL value. Fault Tree Analysis is a method to determine the Probability of Failure on Demand average (PFDavg). Out of 479 designs, there are 276 combinations that have SIL 1 as their level of safety. The price factor is also taken into account in the design, so that by using Analytical Hierarchy Process, the best design can be determined. The best design in terms of the PFDavg value and the price value is a SIS with architecture 1oo2 sensor, architecture 1oo2 logic solver, architecture 1oo1 final element interface, and architecture 1oo1 final element. The design has PFDavg value of 0,014466. SIS is a new layer addition of protection for plant mini flow and able to enhance the overall risk reduction into 60 times greater than without using a SIS. The best design can be simulated using the DCS Yokogawa Centum VP while focusing on the highest risk danger prevention, i.e. to prevent overflowing water on the hot water tank.